PENERAPAN GRAFIK PENGENDALIAN DEMERIT TERHADAP DATA KUALITATATIF - Rusgiyono, Agus (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2009)
A product is represented as inappropriate considered into minor category up to critical, which than given by weight at characteristic of the inappropriate as a according to its importance level. Ploting all amount of inappropriate at one controller graph regardless of type will mislead. To solve it used by graph controller of demerit. Analysis step represent one of the operational step in program operation of quality with a purpose to understand stability and capability of proces wich underway. Expectation of phase analyse can identify the root problem that caused incidence of variation of quality so that can be continued to repair phase. To understand the stability and capability of process which underway can be depicted with controller graph and analysis its. At this article will be studied demerit graph controller and analysis of capability at data qualitative. Keyword : Stability, Capability and Weighted Graph Controller Â